Childhood Neurocysticercosis: Clinico-Radiological Profile and Outcome - Shrestha, BM (Journal of Nepal Paediatric Society, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Neurocysticercosis (NCC) is a major cause of neurological illness worldwide. It is the most common identifiable cause of partial seizure especially in the children of developing world. There is insufficient information about NCC in children in Nepal. This study was, therefore, conducted to evaluate the clinical, neuro-radiographic and therapeutic aspects of NCC in children. Material and Methods: 68 children with this neurocysticercosis were studied prospectively in 20 months in the Lumbini Zonal Hospital (LZH), a secondary-level-referral hospital in the Western Nepal. The diagnosis of NCC was based primarily on the neuro-imaging (CT/MRI) findings. Results: The patients were predominantly females (nearly 65%) with age ranging from 2 to 14 years. Preschool-age children constituted 10% of the patients. The three common manifestations were seizures (91%), headache and or vomiting (38%) and hemi and or monoparesis (15%). CT/MRI demonstrated a single parenchymal ring or nodular enhancing lesion (REL) in 84% of cases with perilesional oedema in nearly 90% of cases. A large majority of patients were treated only with the anticonvulsant drugs (ACDs) for 9 months. Follow-up with repeat CT after 6 months showed a complete resolution of NCC in most of the cases without the need for cysticidal treatment. Conclusion: NCC should be considered first in the differential diagnosis of new-onset seizure among the children of developing countries, where taeniasis is endemic. Most of the patients with NC do not need anticysticercal therapy. Keywords: Seizure, Children, Cysticercosis, CNS, Western Nepal. DOI = 10.3126/jnps.v28i1.1400 J. Nepal Paediatr. Soc. Vol.28(1) p.14-16